Beyond detection: nuclear physics with a webcam in an educational setting. (6th July 2016) - Pallone, A; Barnes, P
Abstract: Basic understanding of nuclear science enhances our daily-life experience in many areas, such as the environment, medicine, electric power generation, and even politics. Yet typical school curricula do not provide for experiments that explore the topic. We present a means by which educators can use the ubiquitous webcam and inexpensive sources of radiation to lead their students in a quantitative exploration of radioactivity, radiation, and the applications of nuclear physics.